Existence and Uniqueness of Solutions for a Coupled System of Higher Order Fractional Differential Equations with Integral Boundary Conditions - Duraisamy, P.; Gopal, T. Nandha (Discontinuity, Nonlinearity, and Complexity, 2026)
In this article, we study the existence of solutions for a coupled system of higher order nonlinear fractional differential equations with non-local integralboundaryconditionbyusing Schaefer’sﬁxedpointtheoremandthe uniqueness result is proved by the contraction mapping principle. Finally, examples are provided to the applicability our main results.